Microstructure and surface characterization of Ni-Cr based composites containing variable solid lubricants - Mohamad, W.F. (Taylor and Francis Ltd., 2020)
Ni-Cr based composites with and without the addition of solid lubricants (MoS2, Ag and CaF2) were prepared by powder metallurgy. The samples were sintered at 1200Â°C in flowing argon atmosphere for 1 hr. The physical properties such as sintered density, relative density and porosity were investigated. Microstructures and phase studies of the Ni-Cr based composites were conducted using SEM analysis. The hardness of the composites was measured by Vickers Micro Hardness Tester. Friction tests were performed with ball on disc configuration following ASTM G-99-95a standard. The MoS2 solid lubricant provided best lubrication at room temperature which was demonstrated by a low friction coefficient compared to pure Ni-Cr composites (0.176 compared to 0.394). The SEM pictures of worn out showed plastic deformation, solid debris distribution, and filling of pores with solid lubricant phases. The time taken for stabilization of friction coefficient also varied with the type of solid lubricant. Dual and multiple addition of solid lubricants reduced the friction of coefficient compared to pure Ni-Cr composite. SEM analysis revealed the spreading of solid lubricants during the sliding test to provide lubrication to both contacting metals.